KEPEMIMPINAN VISIONER KEPALA SEKOLAH, BUDAYA KERJA DAN MOTIVASI BERPRESTASI GURU PENGARUHNYA TERHADAP KINERJA GURU SD PENGGERAK DI KABUPATEN ACEH BARAT - Harizal, Harizal; Marwan, Marwan; Bahri, Saiful; Konadi, Win (LPPM-UNIKI, 2024)
Research to determine the influence of the principal's visionary leadership factors, school culture and teacher achievement motivation on teacher performance. Associative type of quantitative descriptive research method. By using a multiple regression analysis approach. The research was conducted at 8 driving elementary schools in West Aceh Regency. The research results found (a). The level of achievement of the school principal's visionary leadership has reached 93.12%, the level of achievement of school culture that is appropriate and implemented jointly has reached 86.42%. Meanwhile, the principal's assessment stated that teacher achievement motivation was in the very good category, reaching 93.62%, and the teacher's performance level reached 92.29% of ideal expectations. (b) The results of multiple regression analysis conclude that the principal's visionary leadership, school culture and teacher achievement motivation partially have a positive effect on performance, (c). Based on correlation and determination analysis, it is proven that there is a very close relationship and the three factors are R = 0.764. And based on the coefficient of determination, the contribution of the principal's visionary leadership, school culture and teacher achievement motivation to teacher performance is 58.4%